The Relationship between the Role of Parents and the Psychological Readiness of Young Women in Facing Menarche - Ika Hutriana Putri; Nilam Noorma; Indah Nur Imamah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between the role of parents and the psychological readiness of female adolescents to face menarche. This research is a type of correlational quantitative research with a cross sectional design. The research sample was determined by purposive sampling, amounting to 51 grade 5 and 6 students at SDN 002 Tanjung Redeb. Data analysis was carried out using the Spearman Rho test with a significance level of 0.05. Respondents were dominated by 12 years of age (56.9%), were in grade 6 (56.9%), their parents were housewives (47.1%), and their parents' education was high school (54.9%). The average score for the role of parents is 9.31 (st. dev = 1.984) and the psychological readiness of adolescents is 6.98 (st. dev = 1.489). There is a significant relationship between the role of parents and the psychological readiness of young women to face menarche at SDN 002 Tanjung Redeb (p-value 0.000; Corr 0.548).